Vine Water Status Modulates the Physiological Response to Different Apical Leaf Removal Treatments in Sangiovese (Vitis vinifera L.) Grapevines - Tosi, Vincenzo; Palai, Giacomo; Verosimile, Carmine Mattia; Pompeiano, Antonio; D’Onofrio, Claudio (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2025)
Modulating the vine source-sink relationship is a proposed strategy to mitigate the detrimental effect of climate change frequently induced by elevated temperatures and water deficit conditions. In this regard, apical leaf removal could represent a reliable technique, even though its effects on grapevines subjected to different irrigation regimes are unexplored. This study aimed to clarify the effects of apical leaf removal applied before the onset of veraison (ELR) and during berry ripening (LLR, 16 oBrix) on grapevine physiology in vines subjected to full irrigation and water deficit conditions. The irrigation regimes prominently affected the vine physiological parameters over the leaf removal treatments. Both ELR and LLR vines showed transient increases in stem water potential only after the leaf removal. Consistently, the vine transpiration rate was similar between the leaf removal treatments, and even higher water consumption was measured in ELR well-watered vines, associated with new lateral growth. Significant increases in leaf gas-exchange parameters following ELR and LLR were observed only on the measurement dates immediately after the treatment application. However, both ELR and LLR vines consistently exhibited higher daytime net photosynthetic rates than the control, particularly in the afternoon and in the later stages of the season. These conditions led to a significant increase in the leaf total soluble solid concentration in LLR vines subjected to water deficit, which was also associated with a high carbon export rate. Our findings suggest that although apical leaf removal has a limiting effect on reducing the impact of water deficit on vine physiology, it can be an effective agronomic strategy to boost leaf carbon fixation and exportation, particularly when applied during ripening.
Keywords: carbon assimilation; defoliation; transpiration; water deficit